Effects of product recovery methods on the yields and properties of hydrochars from hydrothermal carbonization of algal biomass. (15th January 2023) - Jabeen, Sidra; Gao, Xiangpeng; Hayashi, Jun-ichiro; Altarawneh, Mohammednoor; Dlugogorski, Bogdan Z.
Graphical abstract: Highlights: HTC-derived algal hydrochar was recovered via filtration with and without a solvent. The two recovery methods greatly affect the yields and properties of hydrochar. Under identical conditions, filtration without a solvent gives higher hydrochar yield. The higher hydrochar yield is attributed to the biocrude retained on its surface. Abstract: This contribution reports the effects of product recovery methods on the yields and properties of hydrochars produced from hydrothermal carbonization (HTC) of algal biomass. A slurry of Chlorella vulgaris with 10 wt% of solid loading was hydrothermally carbonized at 180 – 220 °C with holding time of 15 and 60 min. The resulting hydrochars were recovered by two prevailing methods, namely direct filtration and dichloromethane (DCM)-aided filtration. The results indicate that, under identical HTC conditions, compared with DCM-aided filtration, direct filtration always results in higher hydrochar yield because of the biocrude retained on its surface. The presence of residue biocrude in the hydrochars from direct filtration further leads to considerable differences in their properties, as compared with their counterparts from DCM-aided filtration. Specifically, under identical HTC temperature and holding time, DCM-aided filtration yields hydrochars of lower volatile matter contents but higher fixed carbon and ash contents, as compared with the hydrochars from direct filtration. Direct filtration generally recovers hydrochars of greater higher heating values and energy-based yields as compared to DCM-aided filtration. The product recovery methods show considerable impacts on the concentrations of Na, K, Mg, and Ca and their retentions in the hydrochars at 220 °C for 60 min, with higher concentrations and retentions of these elements being observed in the hydrochars from DCM-aided filtration. The hydrochars at 220 °C for 15 and 60 min from DCM-aided filtration show higher specific reactivity of 0.040 – 0.058 min −1 and 0.066 – 0.096 min −1 at hydrochar conversions of ≤ 82 % and ≤ 78 %, respectively, as compared with their direct-filtration counterparts, due to their higher concentrations of catalytic alkali and alkaline earth metals. These findings highlight the importance of considering product recovery methods when comparing the yields and properties of hydrochars from HTC of algae reported in the literature.